From the history of the Noise Control Conference - ENGEL, Zbigniew Witold (Archives of Acoustics, 2010)
In the article a short historical outline of noise control conferences organized in Poland is given. Those conferences with the participation of Polish specialists have been organized since 1964; since 1976 they have been evolved into International Noise Control Conferences. Silhouettes of four Polish scientists, which have made a large contribution to the noise and vibration control in Poland, are presented. Also the current state of threats by noise and vibrations have been briefly mentioned. The significance of such conferences has been emphasized.